2013
DOI: 10.1111/1574-6968.12160
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequences of two dehalogenation specialists- Dehalococcoides mccartyistrains BTF08 and DCMB5 enriched from the highly polluted Bitterfeld region

Abstract: The genomes of two novel Dehalococcoides mccartyi strains, DCMB5 and BTF08, enriched from the heavily organohalide-contaminated megasite around Bitterfeld (Germany), were fully sequenced and annotated. Although overal lsimilar, the genome sequences of the two strains reveal remarkable differences in their genetic content, reflecting a specific adaptation to the contaminants at the field sites from which they were enriched. The genome of strain BTF08 encodes for 20 reductive dehalogenases, and is the first exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 20 publications
3
62
1
1
Order By: Relevance
“…Recently, the genome of strain DCMB5 was sequenced and revealed the presence of 23 rdhAB genes encoding the catalytic subunit A and the putative membrane anchor subunit B, respectively, of reductive dehalogenases (or reductive dehalogenase homologous proteins, Rdh proteins, if not yet biochemically characterized) (7). This finding suggests that the bacterium has a high capacity for organohalide respiration with a broad range of pollutants (8).…”
mentioning
confidence: 99%
“…Recently, the genome of strain DCMB5 was sequenced and revealed the presence of 23 rdhAB genes encoding the catalytic subunit A and the putative membrane anchor subunit B, respectively, of reductive dehalogenases (or reductive dehalogenase homologous proteins, Rdh proteins, if not yet biochemically characterized) (7). This finding suggests that the bacterium has a high capacity for organohalide respiration with a broad range of pollutants (8).…”
mentioning
confidence: 99%
“…All known D. mccartyi strains are obligate hydrogenotrophs and organohalide respirers that reductively dehalogenate a wide spectrum of halogenated organics (3), suggesting broad applicability for the bioremediation of various contaminants. However, despite the isolation and genome sequencing of several strains (D. mccartyi strains 195 [4,5], CBDB1 [6,7], VS [8][9][10], GT [11], BAV1 [10,12,13], BTF08 [14], and DCMB5 [14]), the complete set of enzymes participating in the central electron transport chain (ETC) and the organization of the ETC remain unknown. Previous studies have identified two main classes of enzymes involved in the ETC: reductive dehalogenases (RDases) (5), which pass an electron to halogenated organics, and hydrogenases (H 2 ases), which oxidize the sole known electron donor of D. mccartyi, hydrogen (15,16).…”
mentioning
confidence: 99%
“…None of the dehalogenase genes analyzed were detected in samples grouped in Cluster 5, which consisted of samples deposited at depths below those grouped in Cluster 1 and a surface sample (Aa1). Previous studies demonstrate that Dehalococcoides has multiple reductive dehalogenase genes in addition to tceA, bvcA, and vcrA (Pöritz et al, 2013;Wang, Chng, Chen, Bedard, & He, 2015). Therefore, the samples grouped in Cluster 5 may have contained dehalogenase genes other than the three genes tested in the present study.…”
Section: Spatial Distribution Of Reductive Dehalogenase Genesmentioning
confidence: 73%